CompTIA Network+ review guide - Ferguson, Bill (Serious skills., 2009)
"Serving as a concise, focused study aid to help you prepare for the leading non-vendor-specific networking certification exam, this book features more review questions and study review features than any other guide ... Fully updated for the first revision of the CompTIA Network+ exam since 2005, the book is organized by exam objectives and broken into six parts corresponding to the six domain areas of the Network+ exam: technologies, media and topologies, devices, management, tools, and security"--Resource description page.